Comparative Study on Waterborne Parasites between Malaysia and Thailand: A New Insight - Kumar, T.; Onichandran, S.; Lim, Y.A.L.; Sawangjaroen, N.; Ithoi, I.; Andiappan, H.; Salibay, C.C.; Dungca, J.Z.; Chye, T.T.; Wan Yusoff, W.S.; Lau, Y.L.; Nissapatorn, V. (American Society of Tropical Medicine and Hygiene, 2014)
This study investigated the distribution of parasites as main contaminants in water environments of peninsular Malaysia (October 2011–December 2011) and the southeastern coast of Thailand (June 2012). Sixty-four water samples, 33 from Malaysia and 31 from Thailand, of various water types were examined according to U.S. Environmental Protection Agency guidelines. Drinking or household water types from both countries were free from parasitic contamination. The recreational/environmental (except a swimming pool in Malaysia) and effluent water types from these two countries were contaminated with waterborne parasites: Giardia (0.04–4 cysts/L), Cryptosporidium (0.06–2.33 oocysts/L), hookworm (6.67–350 ova/L), Ascaris (0.33–33.33 ova/L), and Schistosoma (9.25–13.33 ova/L). The most contaminated sites were recreational lake garden 3 in Malaysia and river 2 in Thailand. Higher concentrations of Giardia, Cryptosporidium, and hookworm were found in samples from Malaysia than in samples from Thailand. The presence of Giardia cysts showed a significant association with the presence of Cryptosporidium oocysts (P < 0.005).